2019
DOI: 10.15678/eber.2019.070403
|View full text |Cite
|
Sign up to set email alerts
|

African Immigrant Entrepreneurs in South Africa: Exploring Their Economic Contributions

Abstract: The objective of this article is to determine the economic opportunities created by African immigrant entrepreneurs in South Africa. Furthermore, it is to investigate the impact that Afrophobia has on economic opportunities created by African immigrant entrepreneurs in South Africa. Research Design & Methods:The text utilizes a mixed-methods approach that incorporates both self-administered questionnaire and qualitative in-depth interviews. Through a random sampling approach and snowballing technique, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Majority of immigrant business owners were between the ages of 20-39 (60%) and only 30% were over the age of 40. This is supported by a study on African immigrant entrepreneurs in SA by Ngota et al (2019) who found that there were younger male immigrant entrepreneurs who operated businesses in SA than their female counterpart. The percentages shown above show that young men with tertiary qualifications run their own business at an early age, which is something lacking for their locals' counterparts in the MMM area.…”
Section: Immigrant Participantsmentioning
confidence: 68%
See 3 more Smart Citations
“…Majority of immigrant business owners were between the ages of 20-39 (60%) and only 30% were over the age of 40. This is supported by a study on African immigrant entrepreneurs in SA by Ngota et al (2019) who found that there were younger male immigrant entrepreneurs who operated businesses in SA than their female counterpart. The percentages shown above show that young men with tertiary qualifications run their own business at an early age, which is something lacking for their locals' counterparts in the MMM area.…”
Section: Immigrant Participantsmentioning
confidence: 68%
“…Their prices are very low compared to other shops; they are good in savings & investment, they buy in bulk for discount.' (Participant 06, female, security) Ngota et al (2019) corroborate this by asserting that immigrant entrepreneurs brought competitiveness and innovation. However, it could be understood from these findings that entrepreneurial development may be gained through immigrant entrepreneur's contributions.…”
Section: Nationalitymentioning
confidence: 70%
See 2 more Smart Citations